The role of cGAS-STING signaling in the liver and gastrointestinal system: from signaling networks to target intervention - Tan, Zhengli; Shi, Jiayue; Zhang, Shiyi; Liu, Yanyao (Frontiers in Immunology, 2025)
The cyclic guanosine monophosphate-adenylate synthase (cGAS)-stimulator of interferon genes (STING) signaling pathway constitutes a fundamental mechanism through which the host innate immune system identifies cytoplasmic DNA. This pathway triggers a range of immune responses, notably the production of type I interferon (IFN-I), by detecting both exogenous pathogen-derived DNA and endogenous damage-associated DNA. It plays a pivotal role in anti-infective and anti-tumor responses, as well as in the maintenance of tissue homeostasis. Nevertheless, within the liver and gastrointestinal system—an environment persistently subjected to microbial and metabolic stress—the functionality of the cGAS-STING pathway demonstrates considerable complexity and context dependence. This review provides a comprehensive analysis of the molecular structure and activation mechanisms of the cGAS-STING signaling pathway. It systematically examines the variations in the pathway’s role across different disease contexts, cell types, and modes of stimulation. Furthermore, it synthesizes the latest therapeutic strategies targeting this pathway, offering a theoretical foundation and advanced insights for the development of more precise interventions for liver and gastrointestinal diseases.